Budaya asing dalam kehidupan lokal: Perubahan dan dampak - Nadira, Bella Aina (Maliki Interdisciplinary Journal, 2025)
Globalization has created opportunities for deeper cultural interaction between nations, triggering the influx of foreign cultures into various aspects of local people's lives. This article aims to analyze the influence of foreign culture on local culture, both in positive and negative terms. Positively, foreign cultures bring innovations, technologies and diverse perspectives that can enrich local cultures. However, on the other hand, there are negative impacts such as the displacement of traditional values, cultural homogenization, and loss of local identity. The method used in this research is a literature study, by analyzing relevant literature that examines the relationship between foreign and local cultures in various contexts. The results show that the acceptance of foreign culture is highly dependent on the ability of local communities to filter and adapt foreign elements in accordance with their values. Therefore, a wise strategy is needed so that local culture can be preserved without being closed off from global development.